Free objects in the variety of groupoids defined by the identity xf(x) = f(f(x)) - Celakoska-Jordanova, Vesna (Hikari, Ltd., 2012)
Let V_f denote the variety of groupoids defined by the identity xf(x) = f(f(x)), where f is a fixed nontrivial groupoid power. A description of free objects in this variety and their characterization by means of injective groupoids in V_f are obtained.
Keywords: groupoid, groupoid power, variety of groupoids, free groupoid, injective groupoid